Inhibition Potencies of Phytochemicals Derived from Sesame Against SARS-CoV-2 Main Protease: A Molecular Docking and Simulation Study - Kumar, Anuj; Mishra, Dwijesh Chandra; Angadi, Ulavappa Basavanneppa; Yadav, Rashmi; Rai, Anil; Kumar, Dinesh (Frontiers in Chemistry, 2021)
The ongoing COVID-19 pandemic, caused by SARS CoV-2, is now spread in the nations with high mortality rate and multifaceted impact on human life. The proper treatment methods to overcome this contagious disease are still limited. The main protease enzyme (Mpro also called 3CLpro) is essential for viral replication and has been considered as one of the potent drug targets for treating the COVID-19. In this study, virtual screening was performed to find out the molecular interactions between 36 natural compounds derived from sesame and the Mpro of COVID-19. Four natural metabolites namely, sesamin, sesaminol, sesamolin, and sesamolinol have been ranked as top interacting molecules to Mpro based on affinity of molecular docking. Moreover, stability of these four-sesame specific natural compounds have also been evaluated using molecular dynamics (MD) simulations on 200 nanoseconds. The MD simulations and free energy calculations revealed that these compounds have stable and favorable energies causing strong binding with Mpro. These screened natural metabolites also meet the essential conditions for drug likeness such as absorption, distribution, metabolism and excretion (ADME) properties as well as Lipinski’s rule of five. Our finding suggests that these screened natural compounds may be evolved as promising therapeutics against COVID-19.